Evaluating the relationship between headache and sleeplessness, anxiety, and depression among Hong Kong Chinese women - WU ENQI , WU ENQI; DR. FARRA AIDAHJUMUDDIN, DR. FARRA AIDAHJUMUDDIN (International Journal of Multidisciplinary Research and Studies, 2024)
As research has shown, "In the general population, there is a robust correlation between sleep apnea, headaches, and mood disorders. Daily, morning headaches will be associated with SDBD. Compared to their pre- and post-menopausal counterparts, perimenopausal women are more likely to experience sleep disruptions, headaches, and low mood "counterparts. when compared to "After one month, both Caucasians and Hong Kong Chinese reported lower rates of insomnia (11% versus 29%) (Leger et al., 2000, Li et al., 2002). Within a year, 37% of Hong Kong Chinese and 38% of Whites will suffer from frequent headaches (Cheung, 2000, Hagen et al., 2000). Hong Kong Chinese showed lower rates of depression and greater rates of anxiety (2% vs. 13% and 9% vs. 4%, respectively, in lifetime prevalence) than Caucasians. (Chen et al., 1993; Grant et al., 2005; Hasin et al., 2005). Parker et al. (2001) hypothesize that differences in the prevalence of depression may be due to people's reluctance to admit they have a mental health problem or to the physical manifestations of their symptoms. Because of these differences in prevalence, it is hypothesized that Hong Kong Chinese and Caucasian individuals will have different associations between insomnia, headaches, and mood. The benefits are significant "for the purpose of researching the relationship between insomnia, headaches, and mental health issues amongst the Chinese population of Hong Kong.